2013
DOI: 10.1111/j.1365-2125.2012.04453.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral bioavailability of dabigatran etexilate (Pradaxa®) after co‐medication with verapamil in healthy subjects

Abstract: AIMTo investigate the effect of the P-glycoprotein inhibitor verapamil on the pharmacokinetics and pharmacodynamics of dabigatran etexilate (DE). METHODIn this two part multiple crossover trial in 40 healthy subjects, DE 150 mg was given alone or with verapamil at different doses, duration of treatment (single vs. multiple dosing), formulations, and timings (before, concurrently or after DE). Primary pharmacokinetic endpoints were determined from concentrations of total dabigatran (unconjugated plus conjugated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
132
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 20 publications
5
132
0
11
Order By: Relevance
“…Preliminary data suggest that for P-gp, a single dose of verapamil 120 mg or 80 mg three times daily (total daily doses of 240 mg) for 6 days could improve bioavailability of P-gp substrates or chemotherapy drugs. 52,53 It is noteworthy that clinical trials indicated that the Pgp-modulating agent Valspodar did not improve the treatment outcome of refractory multiple myeloma and P-gp inhibitors may not be a practical solution to MDR. Ceramide, the central molecule of sphingolipid metabolism, generally mediates antiproliferative and proapoptotic functions.…”
Section: Possible Strategies In Clinical Setting 41 Inhibition Of Mmentioning
confidence: 99%
“…Preliminary data suggest that for P-gp, a single dose of verapamil 120 mg or 80 mg three times daily (total daily doses of 240 mg) for 6 days could improve bioavailability of P-gp substrates or chemotherapy drugs. 52,53 It is noteworthy that clinical trials indicated that the Pgp-modulating agent Valspodar did not improve the treatment outcome of refractory multiple myeloma and P-gp inhibitors may not be a practical solution to MDR. Ceramide, the central molecule of sphingolipid metabolism, generally mediates antiproliferative and proapoptotic functions.…”
Section: Possible Strategies In Clinical Setting 41 Inhibition Of Mmentioning
confidence: 99%
“…This is important because the safety and efficacy of dabigatran etexilate are related to its plasma concentrations, single-nucleotide polymorphisms in the gene encoding P-glycoprotein are associated with a 12% increase in peak dabigatran concentration per minor allele carried, studies with other P-glycoprotein inhibitors have found increases in dabigatran exposure ranging from 30% to 171%, and the likelihood of concomitant statin use among these patients is high. [13][14][15][16] We examined the association between statin use and subsequent hospital admissions or emergency department visits for ischemic stroke or major hemorrhage in patients with atrial fibrillation treated with dabigatran etexilate. Owing to their inhibitory effects on P-glycoprotein, we hypothesized that simvastatin and lovastatin would increase the risk of major hemorrhage in patients taking dabigatran.…”
mentioning
confidence: 99%
“…Приведенный в переработанной таблице диапазон влияния верапамила на AUC дабигатрана (+18-143%) менее широк, чем в европейской таблице (+12-180% [3,4]). Исправление внесено потому, что в европейской таблице неверно процитированы ре-зультаты исследования S. Hartter et al [13]. В этом ис-следовании с участием здоровых добровольцев наи-меньшее увеличение AUC дабигатрана (+18%) реги-стрировалось при назначении верапамила немедлен-ного высвобождения (immediate release -IR) по 120 мг 2 раза в день (р/д) спустя 2 ч после приема дабигат-рана.…”
Section: комментарии к переработанной таблицеunclassified
“…Наибольшее увеличение AUC дабигатрана (+143%) наблюдалось при однократном назначении верапамила IR в дозе 120 мг за 1 ч до приема даби-гатрана. Причем в первом случае прирост пиковой кон-центрации дабигатрана составлял 12%, тогда как во вто-ром -179% [13]. Именно два последних показателя (+12% и +179% с округлением до +180%) и были по ошибке включены в европейскую таблицу вместо по-казателей наименьшего и наибольшего увеличения AUC.…”
Section: комментарии к переработанной таблицеunclassified
See 1 more Smart Citation